An overview of Mobile Ad-hoc Simulation tools - Menaka, S; Duraisamy, S (International Journal of Computer Sciences and Engineering, 2025)
Mobile Ad hoc NETworks (MANETs) are dynamic networks, which is populated by mobile stations. Stations in MANETs includes laptops, PDAs or mobile phones. Current types of Wireless Networks are Cellular Networks, Mobile Ad Hoc Network, Wireless Sensor Networks, Vehicle Ad-hoc Networks, and Wireless Mesh Networks. Due to advance in technologies made possibility tremendous usage of small-size and high-performance computing and communication devices like commercial laptops and personal digital assistants. Success of second generation mobile system made more interest in wireless communication. Which led more interest to two types of wireless networks: infrastructured wireless network and infrastructureless wireless network, which is also called Mobile Ad-Hoc Network (MANET). The Infrastructureless wireless network consists of a network with mobile nodes with fixed wired base stations. Simulation tools are used by researchers to debug and test the reliability and Quality of Service of network protocols and also for hardware equipment. This made simulation a very prominent step towards the deployment of wireless communication networks. Hence this paper is very useful to researchers and engineers to propose and bring out new routing protocols using simulator in Mobile Ad Hoc Networks